Breaking news from the HST: the central star of the Stingray Nebula is now returning towards the AGB - Reindl, Nicole (2017)
SAO 244567 is a rare example of a star that allows us to witness stellar evolution in real time. Between 1971 and 1990, it changed from a B-type star into the hot central star of the Stingray Nebula. This observed rapid heating has been a mystery for decades, since it is in strong contradiction with the low mass of the star and canonical post-asymptotic giant branch (AGB) evolution. We speculated that SAO 244567 might have suffered from a late thermal pulse (LTP) and obtained new observations with Hubble Space Telescope (HST)/COS to follow the evolution of the surface properties of SAO 244567 and to verify the LTP hypothesis. Our non-LTE spectral analysis reveals that the star cooled significantly since 2002 and that its envelope is now expanding. Therefore, we conclude that SAO 244567 is currently on its way back towards the AGB, which strongly supports the LTP hypothesis. A comparison with state-of-the-art LTP evolutionary calculations shows that these models cannot fully reproduce the evolution of all surface parameters simultaneously, pointing out possible shortcomings of stellar evolution models. Thereby, SAO 244567 keeps on challenging stellar evolution theory and we highly encourage further investigations.